Quercetin Attenuates Trauma-Induced Heterotopic Ossification by Tuning Immune Cell Infiltration and Related Inflammatory Insult - Li, Juehong; Sun, Ziyang; Luo, Gang; Wang, Shuo; Cui, Haomin; Yao, Zhixiao; Xiong, Hao; He, Yunwei; Qian, Yun; Fan, Cunyi (Frontiers in Immunology, 2021)
Heterotopic ossification (HO) is one of the most intractable disorders following musculoskeletal injury and is characterized by the ectopic presence of bone tissue in the soft tissue leading to severe loss of function in the extremities. Recent studies have indicated that immune cell infiltration and inflammation are involved in aberrant bone formation. In this study, we found increased monocyte/macrophage and mast cell accumulation during early HO progression. Macrophage depletion by clodronate liposomes and mast cell stabilization by cromolyn sodium significantly impeded HO formation. Therefore, we proposed that the dietary phytochemical quercetin could also suppress immune cell recruitment and related inflammatory responses to prevent HO. As expected, quercetin inhibited the monocyte-to-macrophage transition, macrophage polarization, and mast cell activation in vitro in a dose-dependent manner. Using a murine burn/tenotomy model, we also demonstrated that quercetin attenuated inflammatory responses and HO in vivo. Furthermore, elevated SIRT1 and decreased acetylated NFκB p65 expression were responsible for the mechanism of quercetin, and the beneficial effects of quercetin were reversed by the SIRT1 antagonist EX527 and mimicked by the SIRT agonist SRT1720. The findings in this study suggest that targeting monocyte/macrophage and mast cell activities may represent an attractive approach for therapeutic intervention of HO and that quercetin may serve as a promising therapeutic candidate for the treatment of trauma-induced HO by modulating SIRT1/NFκB signaling.